Pengalaman Keluarga dalam Merawat Pasien Pascapasung - Wahyu Reknoningsih; Novy Helena Catharina Daulima; Yossie Susanti Eka Putri (Fakultas Ilmu Keperawatan Universitas Indonesia, 2015)
Pasien pasung yang telah pulang dari rumah sakit jiwa (RSJ) oleh keluarga akan berpotensi untuk dipasung kembali. Tujuan penelitian menguraikan pengalaman keluarga dalam merawat pasien pascapasung. Desain penelitian kualitatif dengan pendekatan fenomenologi. Teknik pengambilan purposive sampling dengan wawancara mendalam. Kriteria inklusi caregiver yang mempunyai anggota keluarga pernah dipasung sebelum dan sesudah dirawat di RSJ dan mampu berkomunikasi. Hasil penelitian menunjukkan bahwa keluarga pasien pascapasung mengalami beban emosional dan kelelahan fisik. Rekomendasi penelitian adalah berupa pengembangan pelayanan keperawatan jiwa di masyarakat dan pemberian pendidikan kesehatan dengan cara penanganan pasien gangguan jiwa dengan perilaku agresif. Abstract Phenomenology Study on the Family’s Experience in Caring for Client Post Restraint (Seclusion) in Central Java. The seclusion or restraint’s client will send home to their family was experienced re restraint or re seclusion. The aim of this study is to elaborate the family’s experience in caring for the client post restraint or seclusion through the qualitative study with the phenomenology approach. The sampling technique is purposive sampling with in-depth interview. The inclusion criteria are the caregiver who has a family member with the experience of being restraint or seclusion before hospitalized, had been restraint, being restraint or being re-restraint, and being able to communicate well. The results show that the family have emotional burden and physical exhausted. This study has suggested that psychiatric nursing may develop a mental nurse psychiatric nursing services in the community by providing health education on how to manage the aggressive behavior of the client with mental disorder. Keywords: the experience, caregiver, restraint (seclusion)